2016
DOI: 10.3310/hta20330
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Acupuncture and Standard carE for pregnant women with Back pain (EASE Back): a feasibility study and pilot randomised trial

Abstract: BackgroundMany pregnant women experience low back pain. Acupuncture appears to be a safe, promising intervention but evidence is needed about its clinical effectiveness and cost-effectiveness.ObjectivesTo assess the feasibility of a future large randomised controlled trial (RCT) testing the additional benefit of adding acupuncture to standard care (SC) for pregnancy-related back pain.DesignPhase 1: a questionnaire survey described current care for pregnancy-related back pain. Focus groups and interviews with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 71 publications
(105 reference statements)
0
30
1
1
Order By: Relevance
“…Western/medical acupuncture is the predominant style of acupuncture used by UK physiotherapists, who use an average of seven acupuncture points per treatment session and aim to elicit the needle sensation of DeQi. The use of a variety of advice and treatment options for the patient described in the vignette is in keeping with previous studies of physiotherapeutic practice in other musculoskeletal conditions, where physiotherapists typically report employing packages of care comprising multiple treatment components [19,20]. Similarly, physiotherapists consider acupuncture as a single component within a package of care, rather than using it in isolation, and several previous studies of acupuncture have shown that it is typically used in combination with other treatment approaches, most often exercise [21].…”
Section: Main Survey Findingsmentioning
confidence: 61%
See 1 more Smart Citation
“…Western/medical acupuncture is the predominant style of acupuncture used by UK physiotherapists, who use an average of seven acupuncture points per treatment session and aim to elicit the needle sensation of DeQi. The use of a variety of advice and treatment options for the patient described in the vignette is in keeping with previous studies of physiotherapeutic practice in other musculoskeletal conditions, where physiotherapists typically report employing packages of care comprising multiple treatment components [19,20]. Similarly, physiotherapists consider acupuncture as a single component within a package of care, rather than using it in isolation, and several previous studies of acupuncture have shown that it is typically used in combination with other treatment approaches, most often exercise [21].…”
Section: Main Survey Findingsmentioning
confidence: 61%
“…The one area in which reported practice differed markedly between professional networks was in the reported use of acupuncture for the patient described in the vignette; respondents from AACP were more likely to report the use of acupuncture (44%) compared with respondents from MIMDTP (9%) and ACPWH (6%) [19].…”
Section: Differences Between Professional Networkmentioning
confidence: 99%
“…To our knowledge, this is the first time that an explicit association between SE and kappa has been reported, although given that the former is a measure of response variability and the latter of agreement, the negative correlation between them would be expected. Indeed, SE-based measures of consensus and dissention for Likert scale data have been suggested before [70,71], although they do not appear to have been used except by their originators. For both datasets (NOW and THEN), a kappa value of 0.4 corresponds to SE of 1.02; thus, an intermediate or better value of kappa, using Fleiss's definitions, corresponds to a SE of 1.02 or less.…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture is part of traditional Chinese medicine and is based on the stimulation of specific sites, known as acupuncture points, on the surface of the body. The most established method of acupuncture uses thin, solid, metallic needles for insertion into the skin, which are then manipulated either manually or by electrical stimulation . This technique is used for diagnostic and/or therapeutic purposes in reversible diseases or disorders that impact on the function of the patient .…”
Section: Introductionmentioning
confidence: 99%
“…The most established method of acupuncture uses thin, solid, metallic needles for insertion into the skin, which are then manipulated either manually or by electrical stimulation. 8 This technique is used for diagnostic and/or therapeutic purposes in reversible diseases or disorders that impact on the function of the patient. 9 Treatment usually comprises insertion of a varying number of needles (up to 30), which are removed after 20-30 minutes.…”
Section: Introductionmentioning
confidence: 99%